Pengaruh Promosi Offline Dan Kualitas Pelayanan Terhadap Minat Beli Konsumen Pada Minimarket Soliamitra Limo Depok - Rizky Saputra; Widya Candra Dewi (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2024)
The aim of this research is to determine the influence of offline promotions and service quality, both partially and simultaneously, on purchasing decisions at the Soliamitra Limo Minimarket, Depok City with a sample of 100 consumers. The method used is a quantitative method. The data analysis used in this research is the classical assumption test, simple linear regression analysis, multiple linear regression analysis, correlation coefficient analysis, coefficient of determination analysis, t test and F test. The results of this research are that offline promotion has a significant effect on buying interest in the Y regression = 5.246 + 0.710 X1, the correlation value is 0.841, meaning that the two variables have a very strong level of relationship. Service quality has a significant effect on purchase interest with the regression equation Y = 4.194 + 0.598 Offline promotions and service quality simultaneously have a significant effect on purchasing decisions with the regression equation Y = 3.263+ 0.289 X1 + 0.391 X2. The coefficient of determination value is 78%, while the remaining 22% is caused by other variables not examined in this research. The test results for the first hypothesis obtained a calculated t value > ttable or (15.392 > 1.661). Based on the results of testing the second hypothesis, the t value obtained > t table or (17.322 > 1.661). Based on the results of testing the third hypothesis, the Fcount value was 172.397 > Ftable 3.090. This shows that simultaneously the variables offline promotion and service quality have a significant influence on purchase interest.